2009
DOI: 10.1039/b802420k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative addition of water to transition metal complexes

Abstract: Possible modes of reactivity of water with transition metal complexes are analysed and examples of oxidative addition of water are discussed in this tutorial review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 34 publications
1
97
0
1
Order By: Relevance
“…As mentioned in the introduction, there are several known mechanisms for water activation, including (1) oxidative addition to a single transition metal center, a binuclear transition metal center, or a geometrically constrained main group element, (2) O−H cooperative cleavage by a transition metal and its supporting ligands, and (3) coordination‐induced weakening of O−H bonds to form H 2(g) . In the current system, we found that O−H bonds of water were cleaved through a unique ligand–ligand cooperation fashion.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the introduction, there are several known mechanisms for water activation, including (1) oxidative addition to a single transition metal center, a binuclear transition metal center, or a geometrically constrained main group element, (2) O−H cooperative cleavage by a transition metal and its supporting ligands, and (3) coordination‐induced weakening of O−H bonds to form H 2(g) . In the current system, we found that O−H bonds of water were cleaved through a unique ligand–ligand cooperation fashion.…”
Section: Methodsmentioning
confidence: 99%
“…We selected a new type of pincer catalyst ( 3 in Scheme ) recently developed by Milstein and co‐workers12 as a template to derive TM‐free analogues. Such TM pincer catalysts have intriguing electronic structures13 (see below) and exhibit high σ‐bond activation reactivity (e.g., involving HH,12a, b CH,12b NH,14a and OH12d, 14b bonds). They promote the direct synthesis of amides and imines from alcohols and amines12c, e, f as well as the sunlight‐driven splitting of water into dioxygen and dihydrogen 12d.…”
Section: Methodsmentioning
confidence: 99%
“…First, the bond dissociation energy of the O-H bond in water is 499 kJ⋅mol -1 , which makes this bond one of the strongest X-H interactions. Second, the strength of the newly formed M-H and M-OH bonds should be sufficient to compensate for the rupture of the water molecule (Ozerov 2009). In this context, it is sensible to elucidate the different modes of water addition to metal centres (Scheme 1).…”
Section: Elementary Stepsmentioning
confidence: 98%